Analisis Pengaruh Kualitas dan Harga Produk terhadap Keputusan Pembelian dan Loyalitas Konsumen Ayam Lokal di Pasar Tradisional Kota Bandung (Survei di Pasar Simpang Dago Kota Bandung) - Malik, Imam; Herlina, Linda; Fitriani, Anita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research aims to analyze the influence of product quality and price on consumer loyalty through purchasing decisions about local chicken at the Simpang Dago Traditional Market, Bandung City. The population in this study was taken from all buyers at Simpang Dago Market, Bandung City with a total sample of 96 people. Sampling was carried out using a nonprobability sampling method with a purposive technique and had criteria, namely consumers who had bought local chicken at Simpang Dago Market, Bandung City at least once. This research method uses quantitative descriptive research with a survey method using interview techniques with a research instrument in the form of a questionnaire. Data analysis techniques used include instrument tests, namely validity and reliability tests, classical assumption tests, namely normality tests, multicollinearity tests, and heteroscedasticity tests, path analysis, and hypothesis testing using the coefficient of determination test, f test, t test, and Sobel test. The research results show that product quality has a direct effect on purchasing decisions by 0.211 and product price has a direct effect on purchasing decisions by 0.054. Product price has a direct effect on consumer loyalty of 0.360 and product quality has no effect on consumer loyalty, while product quality and product price have an indirect effect on consumer loyalty through purchasing decisions of 0.210. This means that purchasing decisions can mediate the relationship between the independent variable and the dependent variable.